Distal femur fractures in adults. Issue 2 (April 2017) - Hoskins, Wayne; Bingham, Roger; Griffin, Xavier L.
Abstract: Fractures of the distal femur occur in a bimodal age distribution. Many are complicated by intra-articular extension and comminution. Periprosthetic fractures add to the complexity of their management. Open fractures can occur with high energy trauma. Surgical treatment is the standard of care, with fixed angle plate fixation and intramedullary nailing being the most common techniques used. Surgical management can be technically challenging. Complications include malunion, delayed union, non-union and implant failure. Persistent disability and poor clinical outcome often results. Despite the development of modern implants, no clear advantage exists for one particular implant and some poorer outcomes may relate to the surgical technique applied to management. Knowledge and correct application of the principles of fracture management are required to optimize the chance of successful outcome. This article will discuss the epidemiology, anatomy, management and surgical techniques for distal femur fractures and review the evidence for the different surgical options.